1999
DOI: 10.1097/00006454-199911000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of serology and 13C-urea breath test for detection of Helicobacter pylori in children

Abstract: The 13C-urea breath test is more reliable than serology for the detection of active H. pylori infection in children. Below 10 years of age serology is insufficiently sensitive for clinical purposes, whereas the 13C-urea breath test remains a reliable test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 24 publications
2
38
0
2
Order By: Relevance
“…Furthermore, as previously shown, the [ 13 C]UBT is an excellent diagnostic test in children 5 years of age and older and can be considered another "gold standard," especially if endoscopy is not indicated (5,7,8).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, as previously shown, the [ 13 C]UBT is an excellent diagnostic test in children 5 years of age and older and can be considered another "gold standard," especially if endoscopy is not indicated (5,7,8).…”
mentioning
confidence: 96%
“…The [ 13 C]UBT has been shown to be an extremely accurate method of detecting H. pylori infection because it has the advantage of evaluating the gastric mucosa as a whole, thereby avoiding the sampling errors inherent in biopsy (4,5,7). Furthermore, as previously shown, the [ 13 C]UBT is an excellent diagnostic test in children 5 years of age and older and can be considered another "gold standard," especially if endoscopy is not indicated (5,7,8).…”
mentioning
confidence: 99%
“…The acceptance of citric acid, another substance that delays gastric emptying, is poor. 12 These factors regarding standardization of the test meal or citric acid ingestion could be another variable that may affect the reliability of UBT. In our study, UBT was performed without any test meal and was shown to be reliable, with 96% sensitivity and 100% specificity.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17] These studies have shown that the UBT is reliable for detecting H. pylori infection. However, reports on the role of the UBT in the assessment of eradication therapy and in the followup evaluation of patients post-treatment have been relatively few.…”
Section: Introductionmentioning
confidence: 99%
“…pylori in children (5,7,23,24,33,42). However, neither has been thoroughly validated for infants, and some studies suggest that both methods may be less accurate in children less than 6 years of age (4,21,23).…”
mentioning
confidence: 99%